Site specific nutrient management through nutriexpert in rice - Sireesha, A; Sreenivas, Ch; Usha Rani , T; Satyanarayana, PV (ORYZA-An International Journal of Rice, 2022)
A field experiment was conducted at Regional Agricultural Research Station, Maruteru, Andhra Pradesh during kharif season of 2016 to study the site-specific nutrient management approaches for enhancing productivity and profitability in rice (Oryza sativa L.). Nutriexpert is a decision support tool developed by the International Plant Nutrition Institute (IPNI). Application of fertilizers based on the Nutriexpert was (112-31-58) higher nitrogen, lower phosphorus and potassium than the recommended dose of fertilizers (90-60-60) during kharif season for rice. The treatments included recommended fertilizer (T1), Site Specific Nutrient Management (SSNM) based on Nutrient expert (T2), SSNM based on Leaf Colour Chart (50% N as basal and rest 50% based on LCC (T3), T2 minus Nitrogen (T4), T2 minus Phosphorus (T5), T2 minus Potassium (T6), Absolute control (without N, P and K) (T7) and Farmer’s Practice (T8) . The results revealed that the highest grain yield (6317 kg ha-1) and straw yield (7663 kg ha-1) of rice was recorded in T2- SSNM (NE) which is significantly superior over all other fertilizer treatments. Application of major nutrients based on nutriexpert recorded higher uptake of nitrogen (128.50 kg ha-1), phosphorus (27.15 kg ha-1), and potassium(137.32 kg ha-1). Nutrient omission and control treatments recorded significantly lowest grain and straw yields of rice and also nutrient uptake. Hence, nutriexpert not only saves the fertilizers but also helps in increased grain and straw yield of rice.